2015
DOI: 10.1063/1.4931095
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the theoretical contact time of a bouncing droplet on the rational macrostructured superhydrophobic surfaces

Abstract: The aim of this study is to reveal theoretically and experimentally a limited contact time of a bouncing droplet on superhydrophobic surfaces with the rationally designed macrostructures. During impacting, the water droplet hydrodynamics is properly altered under the assistance of the macrotextures. As a consequence, the retracting process of the impact water droplet can be completely integrated into the process of spreading out to the maximal deformation, resulting in a limited overall contact time of approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 29 publications
3
76
0
Order By: Relevance
“…B) The impact processes of water droplets on superhydrophobic surfaces with different macrotextures captured by a high‐speed camera. Reproduced with permission . Copyright 2015, AIP Publishing LLC.…”
Section: The Mechanisms Of Anti‐icing and Icephobicitymentioning
confidence: 99%
“…B) The impact processes of water droplets on superhydrophobic surfaces with different macrotextures captured by a high‐speed camera. Reproduced with permission . Copyright 2015, AIP Publishing LLC.…”
Section: The Mechanisms Of Anti‐icing and Icephobicitymentioning
confidence: 99%
“…As shown in Figure b, when the drop impacting on the ridges is much smaller than the drop size, it splits into satellite ones and results in around 37% contact time reduction compared to that on controlled surfaces. Gauthier et al and Shen et al further demonstrated that by the design of macrotexture surfaces with different patterns such as Y‐shape or cross‐shape, drops can be configured into different subunits and leave the surface with a reduced contact time (Figure c) . Recently, Liu et al fabricated curved macrotextures (convex and/or concave) with the curvature of radius comparable to the drop size .…”
Section: Approaches To Enhance Drop Mobilitymentioning
confidence: 99%
“…For example, during the high-speed impact of supercooled (−50°C) water droplets, aircraft surfaces are designed to compel water droplets to rebound off the surfaces before icing. 8 Another example is the fast drop detachment from natural plants and biomimetic surfaces, which significantly decreases the likelihood of virus and bacteria deposition because many pathogens and diseases are transmitted through drops. 9 Other examples include waterproof umbrellas and self-cleaning windshields.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the contact time of the entire impact process is considered to be crucial to these applications. 8 Suitable surface designs could effectively reduce the liquid-solid contact time. [10][11][12][13][14] Artificial superhydrophobic surfaces (SHSs) with contact angles larger than 150°are extremely low-energy surfaces that facilitate rapid drop bounce off due to the low friction between the drop and the substrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation